Sensory systems for robotic applications - Dahiya, Ravinder S.; Ozioko, Oliver; Cheng, Gordon (IET control, robotics and sensors series, 2022)
Thanks to advances in sensing and computer vision technologies, robots can be found today in healthcare, medicine and the industry. Topics covered in this edited book include various types of sensors used in robotics, sensing schemes, sensing technologies and their applications including robotics, prosthetics, wearables and healthcare.